Development of portable water filter device - Azhar, Muhammad Irsyad Zufayri (2025)
Access to clean drinking water is still a serious problem in the world, especially in areas with unstable clean water sources and a high risk of natural disasters. In order to provide clean drinking water from a variety of untreated sources, this study develops a portable water filter system. Designing, creating, and testing a small, effective water filtration system that can eliminate dangerous impurities like bacteria, sediments, and other pathogens are the main goals of this project. With a focus on usability, reliability, and filtration efficiency, the technique covers concept design, material selection, and prototype production. A battery-operated model with a stainless steel construction, a 12V water pump, and an activated carbon and ceramic filtering system was chosen after three design proposals were assessed using a Pugh selection chart.